a3=25
a8=-10
first, a3=25 will be 25= a + (3-1)×d that is the formula of the Arithimetic function genrally→ an=a (which is the first term..that we wanted in this case) + n-1 (n is the order of wanted term..we already has the term which is 3) × d (the common ration).
So, 25=a+(3-1)×d
25=a+2d
25-2d=a rearrange
a= 25-2d
We will take this equation and subsitute it in the other equation which is -10=a+ (8-1)×d
so it will be -10=25-2d+(8-1)×d
-10= 25-2d+7d sum the d
-10= 25+5d
-10-25= 5d
-35=5d
-35/5=d
-7= d
Now that we have the d we can go back to the equation of a= 25-2d and know the value of a
a= 25-2×-7
a1=39
d=-7